2016
DOI: 10.1111/imm.12676
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mucosal immune responses against Helicobacter pylori infection after sublingual and intragastric route of immunization

Abstract: SummaryThere is a current lack of effective mucosal vaccines against major gastroenteric pathogens and particularly against Helicobacter pylori, which causes a chronic infection that can lead to peptic ulcers and gastric cancer in a subpopulation of infected individuals. Mucosal CD4 + T-cell responses have been shown to be essential for vaccine-induced protection against H. pylori infection. The current study addresses the influence of the adjuvant and site of mucosal immunization on early CD4 + T-cell priming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Thus, we believe that the mobilization of neutrophils in blood particularly after SL vaccination might play a role in the polarization of CD4 + T‐cell responses to Th17 responses in the draining lymph nodes. Indeed, we have observed a significantly higher frequency of IL‐17A + cells in the stomach after infection with H pylori in sublingually immunized mice compared with intragastrically immunized mice . We also observed an increase in frequency of CD11b + Ly6G − inflammatory monocytes in the circulation after vaccination particularly after IG route of immunization in accordance with the study by Moyat et al Furthermore, we have previously reported the dependence of IFNγ on the protective immune response after IG immunization, and thus, the CD11b + Ly6G‐ inflammatory monocytes activated after IG route of vaccination might play a role in the polarization of the CD4 + T‐cell response to a Th1 phenotype .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we believe that the mobilization of neutrophils in blood particularly after SL vaccination might play a role in the polarization of CD4 + T‐cell responses to Th17 responses in the draining lymph nodes. Indeed, we have observed a significantly higher frequency of IL‐17A + cells in the stomach after infection with H pylori in sublingually immunized mice compared with intragastrically immunized mice . We also observed an increase in frequency of CD11b + Ly6G − inflammatory monocytes in the circulation after vaccination particularly after IG route of immunization in accordance with the study by Moyat et al Furthermore, we have previously reported the dependence of IFNγ on the protective immune response after IG immunization, and thus, the CD11b + Ly6G‐ inflammatory monocytes activated after IG route of vaccination might play a role in the polarization of the CD4 + T‐cell response to a Th1 phenotype .…”
Section: Discussionsupporting
confidence: 91%
“…Protection in immunized mice only correlated with high frequency of CD4 + α4β7 + cells in the circulation but not with the frequency of neutrophils, inflammatory monocytes or memory CD4 + CD62L − T cells (both SL and IG). Furthermore, in accordance with our previous studies, we also confirmed significantly lower bacterial colonization rates in sublingually compared to intragastrically immunized mice . Altogether, the data presented in the current study will be useful for the design and evaluation of a H pylori vaccine in clinical trials in high‐risk H pylori ‐infected individuals/patients.…”
Section: Introductionsupporting
confidence: 91%
“…Several groups investigated Helicobacter vaccines using mouse models, however, very few tested their protective efficacy. The most commonly investigated vaccine antigens were urease B, neuraminyllactose‐binding hemagglutinin (HpaA), and H. pylori whole cells or lysates …”
Section: Vaccinesmentioning
confidence: 99%
“…Several different adjuvants were used in the published studies, but as in previous years, the most common was cholera toxin B subunit . Bacteria expressing H. pylori antigens, including Lactococcus lactis, Vibrio cholerae, and Bacillus subtilis, were tested as recombinant vaccine vehicles.…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation